Solar Cells: Investigation of Charge Carrier Behavior in High Performance Ternary Blend Polymer Solar Cells (Adv. Energy Mater. 19/2016). Issue 19 (October 2016) - Lee, Tack Ho; Uddin, Mohammad Afsar; Zhong, Chengmei; Ko, Seo‐Jin; Walker, Bright; Kim, Taehyo; Yoon, Yung Jin; Park, Song Yi; Heeger, Alan J.; Woo, Han Young; Kim, Jin Young
Abstract : In article number 1600637, Alan J. Heeger, Han Young Woo, Jin Young Kim, and co‐workers demonstrate high performance ternary blend polymer solar cells including two donor polymers which share the same polymeric backbone. Real charge carrier behavior of ternary blends is firstly clarified via transient absorption spectroscopy as parallel bulk‐heterojunction.